Sanctity of Life and Human Dignity as Human Rights Values Vis-À-Vis The Death Penalty: A Religio-Ethico Reflection - Swartz, Nico P (Advances in Social Sciences Research Journal, 2015)
The paper aims to presents a consistent argument and ideology of life. The study proposes capital punishment as an earthly creation, born out of man’s attempt to find justice according to his own standards – in complete opposition to what God’s perfection intends. Capital punishment is based on the conviction that man must set the ultimate standard of what is right and what is wrong, and that God’s authority is irrelevant to these moral decisions. The paper opted for an exploratory study using literal sources, which the author generated and on which he draws. The article is based on a serious inquiry of original data on the issues of the death penalty, sanctity of life and human dignity. The paper presents a strong, current and relevant theoretical or conceptual framework within which the inquiry is located. The opposition to capital punishment reflects a consistent ethic of life that is evident throughout the Scriptures. The paper finds that sanctity of life and human dignity have become the central argument against the death penalty. It suggests that these two concepts (sanctity of life and human dignity) establish a line that humans or states cannot cross. Every other kind of means which brings human life to a premature end would therefore count as wrong. The research results may lack generalisability in that it focused mainly on a Christian framework. But it can also be viewed as an opportunity for other researchers to test the proposed propositions further, to expand it to the domain of other denominations. But subject to the condition to make this ethic of life that this research holds dear part of their own views.